Higher Order Thinking Skills and Visual Representations of Chemical Concepts: A Literature Review - Basimin, Mudzuna Quraisyah; Habiddin, Habiddin; Joharmawan, Ridwan (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Efforts to assist students in understanding generally abstract chemical concepts are widely done using visual representations as a form of multiple representations in chemistry. This article evaluates and identifies articles from the year (2013-2023) through search engines that provide international services and national journal pages that can be accessed using 4 databases, namely, science direct, eric, google scholar, and crossref. Based on predefined criteria for the use of visual representation in chemistry to improve Higher Order Thinking Skills, 13 relevant articles were obtained. The results of the review show that visual representation can be utilized to train and improve higher-order thinking skills, especially critical, logical, reflective, metacognitive, and creative thinking. Visual representation has also been applied to several approaches or learning models such as Multiple Representation, Particulate Representation, 5R, SWH, Marzano’s Taxonomy, Use of Concept Maps, and PcBL.